COVID-19 Social Assistance Program and Poverty: Evidence from Indonesia - Sri Juli Asdiyanti Samuda; Erna Suprihartiningsih (Department of Development Economics, Universitas Sriwijaya, 2022)
The COVID-19 pandemic and policy response caused widespread disruptions to Indonesia's economy. Besides prioritizing saving people's lives during the COVID-19 pandemic, the government's focus is also to minimize the negative economic impact of the pandemic, including allocating social assistance programs to support household well-being. This study examines the role of COVID-19 social assistance programs in protecting households from falling into poverty during the COVID-19 pandemic. Using a longitudinal dataset from SUSENAS March and September 2020, this study employs difference-in-difference estimation with a conditional logit model to estimate the impact of COVID-19 social assistance programs on household poverty status. The result shows that the COVID-19 social assistance programs positively prevent households from becoming poor during the COVID-19 pandemic.